2018
DOI: 10.11622/smedj.2017094
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric supracondylar humeral fractures: a technique for safe medial pin passage with zero incidence of iatrogenic ulnar nerve injury

Abstract: This safe method of medial pin placement for surgical stabilisation of paediatric supracondylar humeral fractures is easily learnt and reproducible, and produces excellent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
10
0
3
Order By: Relevance
“…Because of the size of our case series, these meta-analyses offer the only studies of comparable size. This case series (to our knowledge, the largest single-technique series) adds substantial support to the growing evidence that the mini-open technique is a safe method of cross-pinning 8,21,24,[40][41][42][43] . The mini-open technique allows for direct visualization of the pin entry site, allowing for much more confident placement than blind placement with palpation.…”
Section: The True Rates Of Iatrogenic Ulnar Nerve Injurysupporting
confidence: 60%
“…Because of the size of our case series, these meta-analyses offer the only studies of comparable size. This case series (to our knowledge, the largest single-technique series) adds substantial support to the growing evidence that the mini-open technique is a safe method of cross-pinning 8,21,24,[40][41][42][43] . The mini-open technique allows for direct visualization of the pin entry site, allowing for much more confident placement than blind placement with palpation.…”
Section: The True Rates Of Iatrogenic Ulnar Nerve Injurysupporting
confidence: 60%
“…Green et al [22]suggested an open medial incision, while Shim et al [23] proposed a subjective technique, putting their thumb over the cubital tunnel. A complex adjustment of the elbow' position combined with repetitive uoroscopy was mentioned in some other studies [28,29]. Michael et al [24] and Shtarker et al [25] applied the nerve stimulator in the medial K-wire insertion.…”
Section: Discussionmentioning
confidence: 99%
“…We also followed these steps while passing the medial pin. Edmonds et al and Woo et al followed the steps given in Tachdjian's Pediatric Orthopaedics textbook by Herring JA regarding safe pin holding, the position of the elbow, and insertion of a medial pin in order to minimize ulnar nerve injury [ 12 , 13 ]. In the year 2018, Woo et al treated 125 children with supracondylar fractures by medial pin fixation first with good results [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Edmonds et al and Woo et al followed the steps given in Tachdjian's Pediatric Orthopaedics textbook by Herring JA regarding safe pin holding, the position of the elbow, and insertion of a medial pin in order to minimize ulnar nerve injury [ 12 , 13 ]. In the year 2018, Woo et al treated 125 children with supracondylar fractures by medial pin fixation first with good results [ 13 ]. There is no study in the literature regarding which K-wire should be placed first so that the reduction stays during fracture fixation with minimal anesthesia time.…”
Section: Introductionmentioning
confidence: 99%